Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/sj.onc.1210787
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between site-specific modifications on p53 and histone H3

Abstract: Previously, we have observed a link between p53 expression and histone H3 post-translational modifications. Here, we ask if specific post-translational modifications of p53 impact upon histone H3 modifications in a selective manner. We have also screened for internal co-operative effects within the repertoire of p53 modifications. Exogenous p53 constructs were expressed in HCT116 p53 À/À cells. Four mutant p53 constructs were used, with single 'phosphorylation' mutations at serines 15 and 37 (S15A, S15D, S37A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 27 publications
(35 reference statements)
5
29
1
Order By: Relevance
“…This suggests that JMJD2B/hKDM4B is a putative target of p53, because other genes are involved in NER, such as DDB1 and XPC (42). In addition, it has been reported that overexpression of p53 generates a reduction in levels of H3K9me2 in cultured human cells (41). Our results are compatible with these reports, because dKDM4B may also demethylate H3K9me2, suggesting that demethylation of H3K9me3 following UV irradiation requires the activation of the dKDM4B gene through Dmp53.…”
Section: Dynamics Of Histone Modifications Insupporting
confidence: 82%
See 2 more Smart Citations
“…This suggests that JMJD2B/hKDM4B is a putative target of p53, because other genes are involved in NER, such as DDB1 and XPC (42). In addition, it has been reported that overexpression of p53 generates a reduction in levels of H3K9me2 in cultured human cells (41). Our results are compatible with these reports, because dKDM4B may also demethylate H3K9me2, suggesting that demethylation of H3K9me3 following UV irradiation requires the activation of the dKDM4B gene through Dmp53.…”
Section: Dynamics Of Histone Modifications Insupporting
confidence: 82%
“…In particular, p53 modulates the transcription of multiple factors involved in DNA repair, apoptosis, and cell cycle arrest (41). In this work, we found that UV irradiation results in an increase in the mRNA and protein levels of the H3K9me3 demethylase dKDM4B.…”
Section: Dynamics Of Histone Modifications Inmentioning
confidence: 49%
See 1 more Smart Citation
“…Mutation of Arg at P −2 positions to S183, T211, S215, and S269 might turn off Aurora-B recognition. It is known that phosphorylation of nearby sites (like S6/S9 and S33/S37) are interdependent [83,84], which is equivalent to perturbations near the phosphorylation site.…”
Section: Resultsmentioning
confidence: 99%
“…It is already established that acetylation at K9 and K14 of histone H3 is associated with the relaxation of chromatin for transcription (22), whereas the acetylation levels at these sites were very low in the SiHa cells (19,23). Although wild-type p53 does not induce acetylation at K9 and K14 of histone H3 (24), it was reported that the presence of p53 likely inhibits K9 deacetylation and facilitates K14 acetylation in response to UV irradiation (23). Therefore, other mechanisms exist by which NDGA induces histone H3 acetylation.…”
Section: Discussionmentioning
confidence: 99%